2002
DOI: 10.1063/1.1456420
|View full text |Cite
|
Sign up to set email alerts
|

Exchange coupling effects in nanocrystalline alloys studied by Monte Carlo simulation

Abstract: The magnetic behavior of nanocrystalline alloys has been modeled using atomic Monte Carlo simulation. The model consists of a cubic lattice composed of a ferromagnetic nanograin in a ferromagnetic matrix. The magnetizations of nanograin core, surface and interface regions and matrix were studied as a function of the exchange coupling between the nanograin and the matrix, as well as of the nanograin/matrix volume ratio, equivalent to the crystalline fraction in the nanocrystalline alloys. The mechanism of polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Recently, the effect of surface anisotropy existed in the surface or interface region of nanograins [15] was reported as an additive contribution to magnetic properties in nanocrystalline alloys, and obviously enhanced by the extension of surface region in grain. Connecting the movement of relative intensity (I) of D 1 and D 2 with grain size (D 0-bcc ), it is found that I ∝ 1/D 0-bcc .…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Recently, the effect of surface anisotropy existed in the surface or interface region of nanograins [15] was reported as an additive contribution to magnetic properties in nanocrystalline alloys, and obviously enhanced by the extension of surface region in grain. Connecting the movement of relative intensity (I) of D 1 and D 2 with grain size (D 0-bcc ), it is found that I ∝ 1/D 0-bcc .…”
Section: Structural Characterizationmentioning
confidence: 99%
“…The as-deposited film and the film annealed at 650 ℃ for 20 min show patterns with broad Bragg lines, centred at about 42° (in 2θ). In most alloys, such patterns are characteristic of a material structure made of small nanocrystals [23][24][25] with topological disorder [26,27] and dominant amorphous-like structure [28]. The broad Bragg lines observed in the patterns suggest the existence of a Cr-Al-C solid solution.…”
Section: X-ray Diffraction Patternsmentioning
confidence: 99%
“…Our patterns show large overlapped Bragg peaks, especially at low temperatures. In intermetallic alloys such large patterns are characteristic of materials with small nano-crystals [9][10][11] with structural disorder [12,13] or predominant amorphous-like structure [14]. Therefore, in order to correctly deconvolute and assign the observed peaks, a refinement fitting procedure had to be performed.…”
Section: Structural Phase Transformationmentioning
confidence: 99%